2020
DOI: 10.1159/000507708
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Waist-to-Hip Ratio and Adverse Outcomes in Heart Failure with Mid-Range Ejection Fraction

Abstract: Background: Waist-to-hip ratio (WHR) is a strong predictor of mortality in patients with heart failure (HF). However, common WHR trajectories are not well established in HF with mid-range ejection fraction (HFmrEF) persons, and their relationship to clinical outcomes remains uncertain. Method: We prospectively enrolled 1,396 participants with HFmrEF (left ventricular ejection fraction 40-49%) from April 2013 through April 2017. The waist and hip circumferences of the subjects were measured at regular intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Although WHR was originally regarded as an indicator for abdominal obesity, its significance in predicting cardiovascular disease and other chronic complications is receiving increasing attention. An increasing WHR has been found to be associated with an increasing risk of myocardial infarction [ 28 ] and heart failure [ 29 ] after adjusting for BMI and other risk factors among those regarded as being very-below-normal weight or of normal weight. Men with the highest-quartile of WHR had multivariate-adjusted hazard ratios of 1.81 for total stroke and 2.26 for ischemic stroke compared with men with the lowest quartile of WHR [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although WHR was originally regarded as an indicator for abdominal obesity, its significance in predicting cardiovascular disease and other chronic complications is receiving increasing attention. An increasing WHR has been found to be associated with an increasing risk of myocardial infarction [ 28 ] and heart failure [ 29 ] after adjusting for BMI and other risk factors among those regarded as being very-below-normal weight or of normal weight. Men with the highest-quartile of WHR had multivariate-adjusted hazard ratios of 1.81 for total stroke and 2.26 for ischemic stroke compared with men with the lowest quartile of WHR [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that WHR was strongly associated with cardiovascular metabolic characteristics, diabetes, coronary prospective cohort study of 1479 participants that higher WHR was independently associated not only with the prevalence of diabetes and the severity of heart failure, but also with higher mortality risk in women (hazard ratio: 2.23, 95% CI: 1.37-3.63, P < 0.05), but not in male participants, and they also found that WHR was positively correlated with inflammatory markers and mitogen-activated protein kinase cascade in female participants, whereas only positively correlated with platelet activity in men (19). Likewise, in a cohort study of 1396 heart failure participants with left ventricular ejection fraction of 40-49%, Gao et al showed that no matter how WHR changed over time, it was still significantly positively correlated with the risk of incident CVD, heart failure and all-cause death (hazard ratio: 2.32-4.03), which also highlighted the importance of long-term management of abdominal fat (33). Although the above studies confirmed the correlation between WHR and CVD and the risk of death, it failed to prove the causal relationship.…”
Section: Discussionmentioning
confidence: 97%
“…These risks were shown later in the context of a wide range of comorbidities. Paradigmatic examples are the associations with type 2 diabetes [29,30], hyperuricemia [31], elevation of free T 3 and MRI-assessed abdominal fat distribution [32], heart failure mid-range ejection fraction [33], and even prevalent or previous metabolic syndrome. These relationships were established by means of different waist circumference-derived indices [34].…”
Section: Discussionmentioning
confidence: 99%